2007
DOI: 10.1016/j.ijmm.2007.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa lipopolysaccharide: A major virulence factor, initiator of inflammation and target for effective immunity

Abstract: Pseudomonas aeruginosa is one of the most important bacterial pathogens encountered by immunocompromised hosts and patients with cystic fibrosis (CF), and the lipopolysaccharide (LPS) elaborated by this organism is a key factor in virulence and both innate and acquired host responses to infection. The molecule has a fair degree of heterogeneity in its lipid A and O-antigen structure, and elaborates 2 different outer-core glycoforms, of which only one binds O-antigen. A close relatedness between the chemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
230
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(235 citation statements)
references
References 167 publications
(172 reference statements)
3
230
0
2
Order By: Relevance
“…It is also involved in the attachment to host cells and it is important for the virulence and pathogenesis of many bacterial species, including Pseudomonas aeruginosa, Salmonella species, and Escherichia coli (66)(67)(68).…”
Section: Biofilms Are Formed On Surfaces Of Living Tissues Medical Dmentioning
confidence: 99%
“…It is also involved in the attachment to host cells and it is important for the virulence and pathogenesis of many bacterial species, including Pseudomonas aeruginosa, Salmonella species, and Escherichia coli (66)(67)(68).…”
Section: Biofilms Are Formed On Surfaces Of Living Tissues Medical Dmentioning
confidence: 99%
“…To date, it is not known precisely which signals in hosts with CF favour and allow for a predominance of mucoid strains compared to non-mucoid strains. In vitro studies, it has been demonstrated that both bacterial phenotypes exhibit similar behaviour and that successive passages in culture media inhibit the expression of the non-mucoid phenotype [4,5].…”
Section: Biofilmsmentioning
confidence: 99%
“…Nutrient gradients occur from the surface of the biofilm to the most internal parts, thereby influencing the bacterial physiology and consequently modifying the speed of growth, the generation time, the susceptibility to antibiotics (due to factors such as the presence of a diffusion barrier to antibiotics), the antigenic variability of individuals, the susceptibility to opsonisation and phagocytosis and even the alginate functions as a negative immunomodulator for the host [4].…”
Section: Biofilmsmentioning
confidence: 99%
“…Alterations in the integrity of the host epithelium during infection may cause life-threatening conditions. In cystic fibrosis (CF), chronic infection of the airways by Pseudomonas aeruginosa leads to severe pulmonary damage and is responsible for mortality and morbidity in the CF population (2). CF is a genetic disease caused by mutations in the CF transmembrane conductance regulator (CFTR) gene that codes for a cAMP-and ATP-regulated chloride channel that is located in glandular and surface airway epithelial cells.…”
mentioning
confidence: 99%